Design and optimization of a baffle-type phase-change heat storage electric heating device. (July 2022) - Hu, Yan; Zhu, Qunzhi; Xu, Shijie; Fu, Zaiguo; Li, Y.
Abstract: Aiming at the phenomenon of excess power and large peak-valley power difference in various application areas, here we design a baffle-type phase change heat storage electric heating device. The device uses expanded graphite (EG)/paraffin (PA) as the heat storage medium, and encapsulates the EG/PA composite phase change materials (CPCM) in a rectangular slab that is directly heated using an electric heating slab. To investigate the impact of the number and thickness of the rectangular plates on the thermal storage and exothermic performance of the device, we perform three-dimensional numerical simulations. We further make performance comparisons with the commonly used shell-and-tube and concentric tube types. In addition, the designed device was optimized by adding fins using the orthogonal test method. To verify the heating effectiveness of the device, we also simulated the temperature field, PMV (Predicted Mean Vote), and PPD (Predicted Percentage Dissatisfied) of the heating room. Our investigations confirm continuous heat release of the device for 7 h during the day which meets home heating requirements. It is also shown that the heat storage and exothermic efficiency reach to 85.83% and 90.1%, respectively, after the device is optimized, the storage and exothermic efficiency increased by 8.15% and 6.43% respectively, and the real-time outlet temperature has increased by 4.98 °C compared with that before the optimization; the average indoor temperature of the heating room is 22.49 °C, PMV is 0.55, and PPD is 15.3% in line with the thermal comfort requirements. The device can realize heat storage and heating at the same time when the power is in the valley, during the peak period, the power supply is turned off and the heating is directly supplied by CPCM. compared with the direct electric heating systems can reduce users' electricity costs, and shift peaks and fill valleys and provide a broad commercialization prospect. The research results provide a reference for the design and optimization of heat storage devices and their application in practical engineering. Highlights: Design and optimization of baffle-type phase change heat storage device. The relationship between the number of HSUs and their thickness was investigated. Performance comparison of baffle-type, shell and tube type and concentric tube type.